Human rights approach to disability within the Malaysian legal, policy and institutional frameworks - Ikmal Hisham Md. Tah (2018)
The legal protection of human rights and people with disabilities have become a global agenda in the 21st century, with the objective to improve the living situation involving persons with disabilities. This minority group is widely stigmatised and discriminated by society, which denies their rights to dignity, equal opportunity and inclusion within society. Because of these violations of human rights, there is the awareness to create proper legal framework in promoting and protecting this group at the international level. The relationship between disability and human rights has began to manifest with the existence of the first human rights treaty, known as the Convention on the Rights of Persons with Disabilities (CRPD), that upholds human rights-based approach to disability. Many states, including Malaysia, have become the State Party to this Convention which would improve the rights of disabled people within their nations. This thesis examines to which extent the Malaysian legal, policy and institutional framework implement human rights-based approach to disability. The stated frameworks include analysis of the constitutional provisions on disability rights, Persons with Disabilities Act 2008, National Disability Policy and Action Plan, and various legislations and institutions related to disability. In addition, the Islamic position on disability rights is discussed to show its compatibility with international law approach to human rights. This thesis largely adopted the qualitative approach of research, which includes doctrinal and non-doctrinal legal research. Besides doctrinal analysis, semi-structured interviews were conducted with twenty-eight (28) respondents in Malaysia, including a Senator representing the disabled community, a national human rights commissioner, policymakers, legal practitioners, disability activists, academicians and experts in disability issues. The analysis has found out that there is inadequate protection of disability rights due to insufficient laws, lack of action-oriented results on the policy and inadequacy of institutional framework which jeopardises the rights. Finally, the research has provided some recommendations to improve the rights of people with disabilities in Malaysia.